FORMULATION AND EVALUATION OF PROMETHAZINE HYDROCHLORIDE BUCCAL TABLETS - R MANIVANNAN; NAVEEN RAJA KANTE (International Journal of Pharma and Bio Sciences, 2012)
Mucoadhesive buccal tablets containing promethazine hydrochloride (25mg) were prepared using polymers such as Carbopol 934P, HPMC K4M and Chitosan in varying concentration by direct compression technique. The Prepared tablets were evaluated for thickness, hardness, friability, and weight variation, uniformity of content, surface pH study, In-vitro swelling study, matrix erosion study, In-vitro bioadhesion study, ex-vivo mucoadhesion time, in-vitro drug release study and stability study. The surface pH of all tablets was found to be satisfactory, close to buccal pH, hence no irritation would observe with these tablets. The formulation (F4) containing carbopol 934P and HPMC K4M in the ratio (1:1) showed good bioadhesive force and maximum drug release of 96.62% for 10 hours. It was observed that the optimized formulation follows korsmeyer-peppas release kinetics. The optimized formulation (F4) was found to be stable upon conducting stability studies as per ICH guidelines at 400C at 75 % RH.